Penerapan Algoritma Cosine Similarity untuk Deteksi Kesamaan Konten pada Sistem Informasi Penelitian dan Pengabdian Kepada Masyarakat - Fajar Agung Nugroho; Fajar Septian; Dimas Abisono Pungkastyo; Joko Riyanto (Teknik Informatika Universitas Pamulang, 2020)
Research and community service activities are the obligations of a lecturer that must be carried out from part of the Tri Dharma of Higher Education in addition to teaching, where research activities should have a level of innovation in the form of development or discovery of something new, but with a large number of lecturers, this results in research activities. and community service has many similarities with previous activities. At the Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Pamulang University, experiencing several problems in the management of research and community service activities, namely the absence of a system used to manage research and community service activities and data related to the track record of research and community service activities that have been carried out by 2,613 lecturers who impact on the difficulty in finding data, efficiency of storage space and more importantly is the number of similar proposals in the research itself. The research carried out aims to develop an information system that can process research and community service activities and detect similarities in content by applying the Cosine Similarity algorithm, so that it can overcome existing problems. The system development method uses a waterfall. From the results of making the system that has been carried out, it shows that the system is capable of processing activities in the field of research and community service carried out by lecturers, supporting storage, and facilitating screening of proposals for research and community service activities that will be approved.